Research on Test-bench for Sonic Logging Tool (2016)
In this paper, the test-bench for sonic logging tool is proposed and designed to realize automatic calibration and testing of the sonic logging tool. The test-bench System consists of Host Computer, Embedded Controlling Board, and functional boards. The Host Computer serves as the Human Machine Interface (HMI) and processes uploaded data. The software running on Host Computer is designed on VC++, which is developed based on multithreading, Dynamic Linkable Library (DLL) and Multiple Document Interface (MDI) techniques. The Embedded Controlling Board uses ARM7 as the microcontroller and communicates with Host Computer via Ethernet. The Embedded Controlling Board software is realized based on embedded uclinux operating system with a layered architecture. The functional boards are designed based on Field Programmable Gate Array (FPGA) and provide test interfaces for the logging tool. The functional board software is divided into independent sub-modules that can repeatedly be used by various functional boards and then integrated those sub-modules in the top layer. With the layered architecture and modularized design, the software system is highly reliable and extensible. With the help of designed system, a test has been conducted quickly and successfully on the electronic receiving cabin of the sonic logging tool. It demonstrated that the system could greatly improve the production efficiency of the sonic logging tool.